(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In this article, protection of the rights and legal interests of women in the society of Uzbekistan, increasing their economic, social and political activity, providing vocational training and employment, wide involvement in entrepreneurship, social support of needy women, ensuring gender equality the ongoing reforms are highlighted